Conservation of small and medium-sized mammals following native woodland regrowth: A case study in a long-term UNESCO Biosphere Reserve, Argentina - Tabeni, Maria Solana (2013)
Land uses such as cattle ranching require important decisions concerning the protection of habitats and species. This is especially true in arid lands and typically involves habitat regrowth as well as the establishment of protected areas. However, the manner in which species respond to the protected area or to the surrounding matrix may vary depending on their ecology, particularly habitat requirements. The objective of this study was to evaluate the role of one such protected dryland area (MaB Reserve of ñacuñán) and adjacent rangelands in the central Monte Desert of Argentina. More specifically, how effective it is in ensuring the conservation of small and medium-sized mammals. Mammal richness and abundance estimated from both trapping and indirect signs were compared in different habitats inside and outside the Reserve. After over 50 years of livestock exclusion in ñacuñán, our results showed significant changes in habitat structure and mammal diversity between protected and unprotected areas. Species associated with high plant cover were found inside the Reserve, while the surrounding areas were occupied by those adapted to open habitats. The presence of the endangered Dolichotis patagonum in rangelands outside the Reserve demonstrates that unprotected areas play a major role in conserving species diversity.